Naturally occurring triterpenic acid from the olea species/ Nur Nabila Fatini Ab Muib ... [et al.] - Ab Muib, Nur Nabila Fatini; Mohsin, Hannis Fadzillah; Ali Shah, Syed Adnan; Abdul Wahab, Ibtisam (Faculty of Pharmacy, 2020)
Olea europaea is originated in the Mediterranean region. It is also commonly known as European olive and is cultivated at various regions since ancient times. From the literatures, the plant has a lot of benefits for common and biological uses. This research covers the general information of O. europaea and the analytical investigations of its chemical compounds. The methodology involved the extraction of the secondary metabolites of the dried leaves, followed by the liquid chromatography of the crude extract and spectroscopic techniques. The characterization of the biomolecule from the chloroform extract revealed the presence of oleanolic acid, a natural triterpenic acid.